CRP 3.4 roots, tubers and bananas for food security and income - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: Aims to increase availability and use of high-quality seed, thus contributing to agricultural development and food security. The Platform uses available information and technologies, brings key stakeholders of seed systems in contact with knowledge, scientific tools and best practices, creates favourable learning conditions and provides the necessary elements for stakeholders to apply this knowledge in decision-making (Gonsalves 2012).